Discrete Mathematics - Johnsonbaugh, Richard ([S.l.] : Prentice Hall, 2014)
Mild revision of top selling text. This text has the best coverage of topics in computer science. New edition features new Mathematician's Corner which is found in each chapter and shows students how to do proofs.